ACAFD: Secure and Scalable Access Control with Assured File Deletion for Outsourced Data in Cloud - Sudha Senthilkumar; Madhu Viswanatham (LPPM ITB, 2014)
Cloud storage has emerged as a popular paradigm to outsource data to third party and share it with the collaborators. While this new paradigm enables users to outsource their sensitive data and reduces data management costs, it brings forth the new challenges to the user to keep their data secure. Data storage security and access control in the cloud is one of the challenging ongoing research works to alleviate the data leakage problem from unauthorized users. Existing solutions that use pure cryptographic techniques suffers from heavy computation work with respect to key management and key distribution. Attribute based encryption is an alternative solution that map the user access structure with the data file attributes to control the data access. However any of the existing schemes doesn't address the access control with assured deletion of the files upon revocation of user access. This article addresses this open issue using a trusted authority that manages the access control list and takes care of key management and key distribution and file deletion upon user revocation. The prototype of model has been presented and analyzed the security features over existing scheme.